PEMANFAATAN BUAH NIPAH DAN KULIT BUAH NAGA MERAH DALAM PEMBUATAN SELAI - Elsa Silvira; Usman Pato (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Jam is semi-solid food made from fruit puree and mixed with 35-45% parts of sugar and heated until the sugar content ranges 50-65%. The study purpose was to get the best ratio of nipa fruit puree and red dragon fruit peel puree in making jam. The research used a Completely Randomized Design Experiment with 5 treatments and 3 replications. The treatments were NM1 (ratio of nipa fruit puree and red dragon fruit peel puree 90% : 10%), NM2 (ratio of nipa fruit puree and red dragon fruit puree 80% : 20%), NM3 (ratio of nipa fruit puree and dragon fruit peel puree 70% : 30%), NM4 (ratio of nipa fruit puree and red dragon fruit peel puree 60% : 40%) and NM5 (ratio of nipa fruit puree and red dragon fruit peel puree 50% : 50%). The data obtained were analyzed statistically using Analysis of Varience (ANOVA) and Duncan’s New Multiple Range Test (DNMRT) at 5% level. The results show that the ratio of nipa fruit puree and red dragon fruit peel puree significantly affected moisture, ash, crude fiber, total dissolved solid contents and the sensory parameters. The best treatment of jam from this research was NM5 with moisture content 34.92%, ash 0.99%, crude fiber 3.18% and total dissolved solid 70.28% brix. The result of descriptive test jam has red colour (4.33), flavour little nipa fruit and red dragon fruit (3.46), stickiness of sticky jam (3.83) and taste little nipa fruit and dragon fruit (3.40). Overall assessment hedonic test of jam was liked by the panelist (4.02). Keywords: jam, nipa fruit, red dragon fruit peel, puree